Analisis Seismisitas Berdasarkan Data Gempa Bumi Periode 1958-2018 Menggunakan b-Value Pada Daerah Selatan Jawa Barat dan Banten - Ilman Luthfi Hilmi; Sutrisno Sutrisno; Dede Sunarya (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2019)
The area of West Java and Banten, especially is Southern is one of the areas prone to earthquakes, caused by the fact that the area is part of the ring of fire path and the presence of faults that are still active faults, such as the Cimandiri Fault, the Baribis Fault and the Lembang Fault. The purpose of this study is to determine the level of seismic activity, the fragility of the rocks and the level of the return period to make earthquake resistant buildings. The seismotechnical parameters of a region can be calculated using the Frequency-Magnitude relationship with the Guttenberg-Rithcher formulation, namely by using the Maximum Likelihood method. Based on the results of the research obtained from the combined data of USGS and BMKG, the magnitude of the 4 SR and the depths of 0-300 km. Based on the analysis and distribution of seismicity, it was found that the higher of the frequency the smaller earthquake magnitude is obtained. The results of the seismotechnical parameters provide variations of the b-value in South West Java and Banten around 0.95-1.45, with the highest value in the South of Pandeglang Regency (1.35-1.45) and the lowest in Tasikmalaya District (0.95-1.05). Variations of the a-values of an area around 6.5-9, while the highest value is in the South of Pandeglang Regency (8.5-9) and the lowest in Tasikmalaya Regency (6.5-7). The Seismicity Index is 0.632 and the Seismicity of the largest earthquakes is 0.004. Probability is at a time interval of 20 years with value as follows P (7.20) = 8%; P (7.40) = 15%; P (7.60); 21%. While variation of the return period are with variations of 5 SR = 1-4 years, 6 SR = 15-55 years and 7 SR = 150-550 years